Mafone : dance theatre for knowledge co-creation - Gruber, Valerie; Ndi, Gilbert Shang (2023)
Theatre, music, dance and poetry performances provide means and methods to co-create knowledges in a way that brings emotional and bodily experiences into dialogue with academic reflections. Working through the trauma of enslavement, colonisation and their aftermath requires such highly sensitive methodologies to avoid further objectification and alienation of the people involved. In this colloquium, we launch a 45-min live recording of the dance theatre “Mafone – Oríkì da viagem” (“Mafone – Oríkì of the voyage”) directed by Brazilian transdisciplinary artist Diego Araúja, Colombian choreographer Jaime Gómez and Mozambican musician Matchume Zango. It is a major outcome of our approach to Orlando Fals Borda’s Participatory Action Research, which inspired us to organise an exchange programme between Afro-descendant artists and community actors from Salvador da Bahia (Brazil) and Cartagena de Indias (Colombia). We take this public video screening as an opportunity to reflect on our shifting roles as researchers, mediators and mentors of this process throughout the past three years, and open up a discussion on the potentials and limitations of combining arts and research. In particular, we consider the opacity through which both trauma and dreams can be reinvented in a non-harmful, but polysemantic way. Hence, we will take the public on a creative journey of transdisciplinary experimentation and collective healing, striving to provoke thoughts and discussions on alternative ways of doing research in and with Latin America.